1979
DOI: 10.1128/aac.16.1.64
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of a New Parenteral Cephalosporin—HR 756: Comparison with Cefamandole and Ceforanide

Abstract: HR 756, a new parenteral cephalosporin that is beta-lactamase resistant, was tested against 271 bacterial isolates. Both agar and broth dilution testing were employed, using two media and two inoculum sizes of bacteria. Antibacterial activity of the drug was compared to that of cefamandole (CFM) and ceforanide (CFN) HR 756 is a new semisynthetic methoxyimino derivative of 7-amino-cephalosporanic acid (2). This parenteral drug is a representative of a newer group of cephalosporin antibiotics which shows relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1980
1980
1983
1983

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Cefamandole, in this and other studies (3,13), has been shown to have good in vitro activity against gram-positive cocci VOL. 19,1981 on April 7, 2019 by guest http://aac.asm.org/ Downloaded from (2,14,26) and moxalactam (7,15,25). Ro and cefotaxime were approximately equal in activity, with moxalactam being only slightly less active.…”
Section: Discussionmentioning
confidence: 97%
“…Cefamandole, in this and other studies (3,13), has been shown to have good in vitro activity against gram-positive cocci VOL. 19,1981 on April 7, 2019 by guest http://aac.asm.org/ Downloaded from (2,14,26) and moxalactam (7,15,25). Ro and cefotaxime were approximately equal in activity, with moxalactam being only slightly less active.…”
Section: Discussionmentioning
confidence: 97%
“…Although secondgeneration cephalosporins-cefoxitin, cefamandole, and cefuroxime-inhibit the majority of Enterobacteriaceae, they have little or no activity against Pseudomonas aeruginosa. Third-generation compounds now being tested include cefoperazone (T1551) (5) and cefotaxime (HR756) (1,2,3,8). Moxalactam (LY127935) (4) and another new beta-lactam antimicrobial agent, thienamycin (11), though not cephalosporins, resemble them in that spectrum of activity and are currently under study.…”
mentioning
confidence: 99%
“…In one instance, lesions were extensive and may have contributed to the death of the patient. The pathogenesis of the pseudomembranous changes could not be inferred from In vitro susceptibility testing (4,5,7,14,20,22,23,25,26) and results obtained in this study suggest that the greatest benefit of cefotaxime might occur in the treatment of multiply resistant, nosocomial, gram-negative pathogens. Fifteen courses of cefotaxime administered for infections caused by multiply resistant Serratia marcescens (13) (15).…”
Section: Resultsmentioning
confidence: 88%
“…One such agent, cefotaxime (Claforan, HR756; Hoechst-Roussel Pharmaceuticals, Sommerville, N.J.), has been shown to have excellent in vitro activity against Enterobacteriaceae and good activity against grampositive cocci (4,5,7,20,23). In vitro activity against strains of Pseudomonas aeruginosa has been comparable to that of ticarcillin, whereas the susceptibility of strains of Bacteroidesfragilis has been variable (2,4,14,22,25). Published information regarding the clinical efficacy of cefotaxime is limited.…”
mentioning
confidence: 99%